Acoustic heating of the polar night mesosphere - Maeda, Kaichi.; Goddard Space Flight Center.; United States. National Aeronautics and Space Administration. (Washington, D.C. : National Aeronautics and Space Administration, 1963)
Prepared at Goddard Space Flight Center. "N64-10398." Includes bibliographical references (p. 19-21). Mode of access: Internet.